The influence of design methodology on a designer's emotional parameters and on design results (2016)
This paper presents the results of an experiment carried out on 21 subjects, all of whom had an engineering background, with the aim of determining the influence of the designer’s attitude on the design process and on the finished design. The participants were asked to solve a range of design problems by employing different methods while their emotional response parameters were being registered by a noninvasive neuroheadset. The recorded data was used firstly to compare the different reactions of the subjects when using different design methods. A second analysis was carried out to determine whether the variations in the emotional parameters bore any direct relation to the creativity of the outcomes. The results obtained indicate a relation between emotional parameters, individuals and the design method used. However, there does not appear to be any direct association between emotional parameters and the creativity of the results.